Ethiopia Alive & Thrive Baseline Survey 2010: Community - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is the result of the community survey that was conducted to gather data at baseline as a part of the impact evaluation of the Alive & Thrive (A&T) interventions in Ethiopia. The broad objective of the impact evaluation in Ethiopia is to measure the impact of A&T’s community-based interventions, delivered through the government's health extension program (HEP) platform, in the reduction of stunting and improvement of IYCF practices in two regions where the IFHP operates, namely Tigray and SNNPR (Southern Nations, Nationalities, and People’s Region). A&T is a six-year initiative to facilitate change for improved infant and young child feeding (IYCF) practices at scale in Bangladesh, Ethiopia, and Viet Nam. The goal of A&T is to reduce avoidable death and disability due to suboptimal IYCF in the developing world by increasing exclusive breastfeeding (EBF) until 6 months of age and reducing stunting of children 0-24 months of age. The Ethiopia baseline survey had two broad objectives. The first objective was to gather data on the primary impact indicators of the evaluation, prior to implementation of any A&T interventions, to establish a baseline against which changes would be measured. The second objective was to assess different factors that may influence the outcomes of interest, and thus shape the impact of the primary impact indicators. These factors were determined at five different levels: 1) child, 2) maternal/caregiver, 3) household, 4) community, 5) health care providers, 6) health system. These factors will also provide useful information to interpret the results of the impact evaluation and also signal key issues to pay attention to in the process evaluation. The Ethiopia baseline survey used five separate questionnaires that aimed to capture elements along the program impact pathways. These tools include 1) a household questionnaire, 2) a staff questionnaire of HEWs, 3) a staff questionnaire of supervisors of HEWs, 4) a VCHP), and 5) a community questionnaire. The community questionnaire provided information on the following: 1) general characteristics of the cluster: population, number of households’ languages, livelihood, season of food shortage, topography; 2) infrastructure: access to main road (both during dry and rainy season), electricity, access to clean water; 3) distance from the nearest major town, type of transportation used to reach this town; 4) access to the nearest market; 5) migration pattern; 6) social and food assistance, such as presence of productive safety net program, community-based nutrition program, etc.; 7) natural disaster occurring in the area during the three years before the survey; 8) availability and access to health services: health post, government hospital, private clinic, etc.; 9) availability of education facility: junior and high school, college. The community questionnaire was administered to a group of community members to gather information on the contextual factors related to each community as well as to understand differences in community characteristics across the clusters (enumeration areas (EA)). This information at the community level is critical to control for externalities that could influence the outcome of the program.